2016
DOI: 10.1038/srep23058
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing of continuous-fiber composites by in-nozzle impregnation

Abstract: We have developed a method for the three-dimensional (3D) printing of continuous fiber-reinforced thermoplastics based on fused-deposition modeling. The technique enables direct 3D fabrication without the use of molds and may become the standard next-generation composite fabrication methodology. A thermoplastic filament and continuous fibers were separately supplied to the 3D printer and the fibers were impregnated with the filament within the heated nozzle of the printer immediately before printing. Polylacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
507
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 896 publications
(519 citation statements)
references
References 39 publications
3
507
0
9
Order By: Relevance
“…Recently, it has been demonstrated that 3D printing technology can be used to produce materials with finely tuned structural properties [31,32]. In the near future it may also become possible to realize experimentally the limit of high disorder studied here.…”
Section: Localized Load Sharingmentioning
confidence: 98%
“…Recently, it has been demonstrated that 3D printing technology can be used to produce materials with finely tuned structural properties [31,32]. In the near future it may also become possible to realize experimentally the limit of high disorder studied here.…”
Section: Localized Load Sharingmentioning
confidence: 98%
“…This trend could be further supported by adopting new far more diverse polymer recycling codes to further expand the materials selection while reducing costs [94]. In addition, there is a large potential for research into new composite filaments with TPE as the matrix and carbon or steel fiber as reinforcement [105][106][107][108][109]. This could open new possibilities for 3-D printing belts that do not stretch and deform (while enabling the RepRap community one step closer to complete self-replication).…”
Section: Likelihood Of a Consumer Buying A 3-d Printer For Savingsmentioning
confidence: 99%
“…Due to this reason they are used very often as safety shields for engine cowls. Lot of research work is being carried out on additive manufacturing of composites reinforced with aramid fibre for their application in aerospace engineering [53].…”
Section: Glass Fiber Reinforced Compositesmentioning
confidence: 99%